Exponential mixing for stochastic 3D fractional Leray-α model with degenerate multiplicative noise. (September 2019) - Li, Shihu; Liu, Wei; Xie, Yingchao
Abstract: In this work we establish the exponential mixing property for stochastic 3D fractional Leray- α model with degenerate noise. The main result is also applicable to stochastic 3D hyperviscous Navier–Stokes equations and stochastic 3D critical Leray- α model.